Editor's Note - Devi, S. Susela; Quah, Chee Heong (Asian Journal of Business and Accounting, 2013)
It is our pleasure to present to you the first issue of Volume 6 of the Asian Journal of Business and Accounting (AJBA). The journal made its debut in 2008 and has continued to publish research work from scholars within Asia and elsewhere relating to issues in the Asian region. We are encouraged by submissions from scholars from many parts of the world and the growing interest in business and accounting research in this region. We are particularly pleased to receive papers from Asia, especially, the emerging economies. In this issue we have included papers from Philippines and Iraq. AJBA is now indexed in SCOPUS, ERA 2012, and MyCite (25/112) 5 year impact factor of 0.063. It is also currently under review by Thomson Reuters Web of Science. We are hopeful given the rigour and quality of papers that have been published and also currently under review, that AJBA will soon succeed in its endeavour to be indexed in the Thomson Reuters Web of Science. In this issue five articles are presented. The first is an extract of a public lecture by Professor Jeffrey Sachs at the Faculty of Business and Accountancy, University of Malaya. It details Professor Sach’s exploration of the four fundamental drivers to global change: economic convergence, rapid technological transformation, inequality and environmental crises. He articulates the importance of sustainable development and its implications for Asia. Next, Racelis (2013) attempts to develop a virtue ethics scale for managers using the context the Philippine managers. He demonstrates that virtue theory is an improved ethical paradigm for businesses and that it is possible to augment teleological and deontological ethics scales with a virtue ethics scale to create awareness of the virtuous qualities entrepreneurs and managers. This can pave the way for further investigations of the strategic role of virtue ethics theory in the Asian business environment. The next three papers are in line with the first driver of global change emphasised by Professor Sachs in the first paper. In the context of economic convergence, Lallo and Selamat (2013) address the challenges of global educational reforms. They examine the factors impacting the Iraqi experience in developing an Accounting Information System course that meets international standards. The Iraqi framework is useful for reflection by educators from the Asian region as they attempt to convergence, specifically in accounting and financial reporting. The issue of international accounting convergence is addressed by Pawsey, Brown and Chatterjee (2013) who examine the responses to the U.S. Securities Commission’s proposal to allow U.S. listed companies to prepare financial statements following the International Financial Reporting Standards (IFRS). The paper is useful for reflection by researchers and regulators in Asian region as most Asian countries have embarked on this convergence agenda. The implications for the Asian region are discussed in this paper. The final paper, Phang and Mahzan (2013) investigate the Malaysian experience in converging to IFRS. They identify the external drivers that influence the readiness of Malaysian listed firms for IFRS convergence. They draw upon Institutional theory to explain IFRS convergence in Malaysia. The paper provides insights to researchers from emerging economies and suggests strategies to regulators and other stakeholders in the financial reporting process to facilitate the convergence process. In conclusion we thank all our area editors, members of the editorial board and advisory board and reviewers for their continued support and encouragement. We hope this issue brings AJBA closer to achieving its mission to incrementally provide a voice for scholars embarking on Asia-focused research.